Investigação das alterações da parede celular de mamoeiros (Carica papaya L.) infectados pelo Papaya meleira virus (PMeV) - Dutra, Jean Carlos Vencioneck (2015)
Papaya sticky disease, caused by Papaya meleira virus (PMeV), is an important papaya disease in Brasil and Mexico due the severe economic losses it causes. Studies to assess the pathogen-host interaction at a histological are fundamental in order to understand the mechanisms that underlie natural resistance. In this study we collected leaves of healthy and symptomatic papaya sticky diseased plants and observed the topography and mechanical properties of plant cell walls by atomic force microscopy (AFM). Two-dimensional images obtained from different areas of the cell wall showed that the cell walls of healthy plants are smoother than the walls of sticky diseased plants. Also healthy plants displayed higher constitutive characteristics of the cell wall than diseased plants and the average maximum adhesion force was higher on healthy plants than on diseased plants. PMeV promotes changes on cell walls, making them more fragile and susceptible to breakage. These changes, associated with increased water uptake and internal pressure of laticifers causes cell disruption that leads to spontaneous exudation of latex and facilitates the spread of PMeV to other laticifers. The results of this work provide new insights on the interaction papaya-PMeV which could prove helpful when trying to understand and control the papaya sticky disease.